The presence of circular (bio)economy in the environmental investment projects of the Western Balkan countries - Molnar, Dejan; Josipović, Sonja; Rikalović, Milena (Industrija, 2024)
The uncontrolled use of natural resources, loss of biodiversity and natural capital, pollution of water resources, CO2 emissions, inadequate waste disposal and other environmental problems have influenced the growth of investments in the development of green technologies, as well as the development of more efficient methods in terms of the use of resources to increase productivity in different sectors of the economy without endangering the land and biodiversity. The paper examines the advantages of developing the investment projects that promote the concepts of green (bio)economy and circular economy and ensure profitability without a negative impact on the natural environment. The innovation projects supported by the Western Balkans Investment Framework in the field of energy, environment, transport, social protection and digital infrastructure are analyzed. It is concluded that about 50% of the supported projects are environmental projects that aim at providing environmental benefits or preventing the environmental damage. Special attention is paid to the environmental projects co-financed by the Innovation Fund of the Republic of Serbia.
Keywords: Bioeconomy, innovations, projects, economic methods, Western Balkans.